Food Production and Consumption in Cameroon - Leypey, Mathew Fomine Forka (Petits Propos Culinaires, 2018)
This article presents a preliminary survey of the precolonial and contemporary evidence for the patterns of cultural and commercial relationships established through food production and consumption in multiple ethnic groups in Cameroon. The sampled groups have been carefully selected to form a north/south transect running the length of the country. From the shores of the Atlantic Ocean in the South West Region to the Lake Chad basin in the north, the groups are Bakweri, Mbo, Bamum, Wawa, Doowaayo, and Kotoko. The members of these ethnic groups exchanged (and continue to exchange) different food items in cultural and commercial spheres.